Vous êtes sur la page 1sur 1

 

[a; b]

(a < b)

   

1

ba 1 [a,b] (x)

 

f (x) = E(x) = a+b

2

 

[a, b]

V

ar(x) = (ba) 2

12

λ

λ > 0)

   

f (x) = λe λx 1 R +(x) E(X) =

1

λ

 

V

ar(X) =

1

λ

   

2

N (m, σ 2 )

   

f (x) = E(X) = m

σ 2π exp((xm) 2

1

2σ 2

)

V

ar(X) = σ 2

 

Γ(n, λ)

   

λ

(n1)! e λx (λx) n1 1 R +(x)

(n N)

f (x) = E(X) = n

λ

 

n λ

V

ar(X) =

n

λ

 

2

   

1

 

f (x) = 1

π 1+x 2

 

 

B(p)

 

P

(X = 1) = p P (X = 0) = 1 p

E(X) = p

 

V

ar(X) = p(1 p)

 

B(n, p)

 
 

k

n B(p) n

P(X = k) = C E(X) = np

n

p k (1 p) nk

V

ar(X) = np(1 p)

 

P oi(λ)

 

P(X = k) = e λ (λ) k

k!

E(X) = λ

 

V

ar(X) = λ

   

   

P

(X = k) = p(1 p) k1

E(X) = 1

 

V

p

ar(X) = 1p

p

2